2021
DOI: 10.1002/1878-0261.13068
|View full text |Cite
|
Sign up to set email alerts
|

VprBP directs epigenetic gene silencing through histone H2A phosphorylation in colon cancer

Abstract: Histone modification is aberrantly regulated in cancer and generates an unbalanced state of gene transcription. VprBP, a recently identified kinase, phosphorylates histone H2A on threonine 120 (T120) and is involved in oncogenic transcriptional dysregulation; however, its specific role in colon cancer is undefined. Here, we show that VprBP is overexpressed in colon cancer and directly contributes to epigenetic gene silencing and cancer pathogenesis. Mechanistically, the observed function of VprBP is mediated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 45 publications
(59 reference statements)
10
39
0
Order By: Relevance
“…Antagonists that disrupt protein–protein interactions between DCAF1 and its interacting partners could be used toward development of therapeutics for cancers when DCAF1 is overexpressed, and HIV when DCAF1 is hijacked by the virus. , In these cases, the small molecule prevents the binding of Vpr and Vpx to DCAF1, for example, preventing viral hijacking of the CRL4 DCAF1 or EDVP DCAF1 complexes. Another potential application of antagonizing CRL4 DCAF1 function is in Merlin-deficient tumors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antagonists that disrupt protein–protein interactions between DCAF1 and its interacting partners could be used toward development of therapeutics for cancers when DCAF1 is overexpressed, and HIV when DCAF1 is hijacked by the virus. , In these cases, the small molecule prevents the binding of Vpr and Vpx to DCAF1, for example, preventing viral hijacking of the CRL4 DCAF1 or EDVP DCAF1 complexes. Another potential application of antagonizing CRL4 DCAF1 function is in Merlin-deficient tumors.…”
Section: Resultsmentioning
confidence: 99%
“… 25 H2AT120 phosphorylation (H2AT120p) by DCAF1 is associated with gene silencing at tumor suppressor genes, 25 and overexpression of DCAF1 and H2AT120p has been shown to cause proliferation of colon cancer cells. 26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, BIX01294 was further demonstrated to synergize strongly with HDAC inhibitors to induce chicken HDP gene expression [ 47 ]. B32B3, a compound that blocks VprBP-mediated phosphorylation of histone 2A [ 48 ], is also a weak HDP inducer. Identification of different classes of epigenetic compounds with the HDP-inducing activity has provided new options for host-directed antimicrobial therapy, although the mechanism by which many of these compounds trigger HDP gene expression remains largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“… 345 The VprBP inhibitor B32B3 is able to reduce colonic organoid growth by blocking H2AAT120p and activating the normal transcriptional program. 346 Human pancreatic islet organoids respond to the HIF-1α inhibitor PX-478, and long-term exposure to high glucose increases the glucose-induced insulin secretion stimulation index, suggesting that the HIF-1α inhibitor PX-478 has the potential to act as an antidiabetic agent. 347 AT-rich interacting domain 1 A (ARID1A), an important subunit of the chromatin remodeling complex, carries a heterozygous mutation in most human GC cases, and tumor organoids with ARID1A heterozygosity show growth inhibition by combination therapy with TP06 and Nutlin-3, an epigenetic inhibitor and a p53 agonist, respectively, offering a new option for GC therapy.…”
Section: Digestive System Organoid Models and Precision And Personali...mentioning
confidence: 99%